UPAYA GURU DALAM MENINGKATKAN ETIKA BERDO’A MELALUI CERITA DENGAN MEDIA GAMBAR PADA ANAK - Solimah, Solimah; Marmawi, Marmawi; Miranda, Dian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract: The purpose of this research is: To get information about the increased ethics pray through the story with pictures media in children aged 5-6 years in RA. Nurul Muslimin Kubu Raya Sungai Raya. This classroom action research was conducted in two cycles. Each cycle consists of planning, implementation, observation, and reflection. The method used is descriptive method with the form of classroom action research study. Sources of data in this study is numbered 23 children. The collection of data by using data and observation guidelines. Based on the research that has been done: 1) Planning of learning undertaken by teachers in improving ethics pray through the story with media images of children aged 5-6 years in RA. Nurul Muslimin Kubu Raya Sungai Raya has been planned very well, 2) Implementation of the learning undertaken by teachers in improving ethics pray through the story with media images of children aged 5-6 years in RA. Nurul Muslimin Kubu Raya Sungai Raya has been performing very well, 3) Having given the story by drawing increased media ethics pray in children aged 5-6 years in RA. Nurul Muslimin Kubu Raya Sungai Raya. Increased pray ethics is categorized as very goodKeywords : Pray Ethics, Media Stories with Pictures